Belief on The Purpose of Religion According to Quranic Perspective Amongst Malaysian Public University Students - Mohammed Zabidi, M. (Universiti Sains Islam Malaysia, 2024)
Islam teaches its adherents to practice the noblest forms of ethics and morality called Akhlak. Akhlak or Islamic ethics and morality provide peace in human life, whether to an individual or the community and portray the image of Islam as a religion of mercy for all. However, in the context of UiTM students where Malay Muslims are the majority, the rise in problems related to unethical behaviors among them poses an important question, what do the Malay Muslims in Malaysia understand about being a Muslim? What are their beliefs about the purpose of professing the Islamic faith? By taking a group of UiTM students who are largely composed of Malay Muslims, this study analyses their level of belief regarding the purpose of religion. A total of 1313 students from all UiTM branches in Peninsular Malaysia were selected as respondents through the group strata sampling technique. Data from the questionnaire were analyzed using SPSS (Version 12.0). Frequencies, percentages, and means were reported for each sub-construct. The study concludes that students’ belief about the purpose of religion is still tied to aspects of cultural, ritual and customs. Hence, the inculcation of students’ belief in religion should be reinforced by the understanding of the basic essentials of Islam and the Unity of God (Tawhid) so that students recognise and acknowledges with certainty that the purpose of religion is to accomplish the goal of creation and to realise the original covenant entered with Allah SWT in the day of alastu. Belief in the purpose of religion should be linked to the goals of creation and to the covenant made.